2019
DOI: 10.1039/c9ra08408h
|View full text |Cite
|
Sign up to set email alerts
|

Collective absorption of 2,4,6-trinitrotoluene into lipid membranes and its effects on bilayer properties. A computational study

Abstract: The widely used explosive, 2,4,6-trinitrotoluene (TNT), is a highly toxic chemical, which can cause hepatitis, cataracts, jaundice and so on, in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Therefore, for the sake of an excellent ecological environment and human health, numerous works have been done on the adsorption, detection, biodegradation, and catalytic oxidation of TNT in recent years. Xiong et al reported a molecular cage that can hold two TNT molecules, and the molecular cage is composed of two TPE trimeric macromolecules, which can detect residual TNT in the environment. Krishna et al proposed to use polyethyleneimine-modified MnO 2 nanosheets to efficiently detect TNT and other substances.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for the sake of an excellent ecological environment and human health, numerous works have been done on the adsorption, detection, biodegradation, and catalytic oxidation of TNT in recent years. Xiong et al reported a molecular cage that can hold two TNT molecules, and the molecular cage is composed of two TPE trimeric macromolecules, which can detect residual TNT in the environment. Krishna et al proposed to use polyethyleneimine-modified MnO 2 nanosheets to efficiently detect TNT and other substances.…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods proposed so far, the Marrink–Berendsen (MB) method is one of the best‐known methods used to calculate the position‐dependent diffusion coefficient 21–26 . This method allows for straightforward calculation of the position‐dependent diffusion coefficient with existing MD calculation packages.…”
Section: Introductionmentioning
confidence: 99%
“…Two of us and other coworkers have also previously proposed a method for obtaining the positiondependent diffusion coefficient with high accuracy in any heterogeneous system 20 . Among the methods proposed so far, the Marrink-Berendsen (MB) method is one of the best-known methods used to calculate the position-dependent diffusion coefficient [21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%